Culture, Culturalism Art and Cultural Age and Cultural Development of the Child in the Light of Leo S. Vygotski’s Views - Zaorska, Marzenna Ewa (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
The issue of cultural development, cultural development, perception of art, which is part of human cultural development, is an important issue in the field of possible theoretical analyzes and related practical activities. One of the psychological concepts in which reflections on signaled relationships are present is the concept proposed by the Russian psychologist L.S. Vygotsky. Therefore, the purpose of this article is to point out the selected theses from the views of the learned scientist on the broadly understood issue of cultural development of human beings in connection with the historical and cultural development of humanity as well as factors determining that development.